2011
DOI: 10.1080/14703297.2011.564020
|View full text |Cite
|
Sign up to set email alerts
|

Service users and carers: preparing to be involved in work‐based practice assessment

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Consistent with previous studies, the narratives revealed that although service users had been given a voice in students' assessments (Dearnley et al, 2011;Debyser et al, 2011;Duffy et al, 2013;Muir and Laxton, 2012;Skilton, 2011;Skoura-Kirk et al, 2013;Stacey et al, 2012;Stickley et al, 2010;, summative assessment decisions that affect progression remained with social work academics (Skilton 2011;Skoura-Kirk et al, 2013). The study findings, albeit with a small sample, concur with prior research in relation to both academic and practice assessments of students.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with previous studies, the narratives revealed that although service users had been given a voice in students' assessments (Dearnley et al, 2011;Debyser et al, 2011;Duffy et al, 2013;Muir and Laxton, 2012;Skilton, 2011;Skoura-Kirk et al, 2013;Stacey et al, 2012;Stickley et al, 2010;, summative assessment decisions that affect progression remained with social work academics (Skilton 2011;Skoura-Kirk et al, 2013). The study findings, albeit with a small sample, concur with prior research in relation to both academic and practice assessments of students.…”
Section: Discussionsupporting
confidence: 81%
“…Although it was beyond the scope of this study to explore patient involvement in health education more broadly, the studies in Nurse Education Today reported that, despite the growing body of literature on service user involvement in the medical and social care professions, there were only limited studies exploring their involvement in students' assessments (Dearnley et al, 2011;Debyser et al, 2011;Muir and Laxton, 2012;Stacey et al, 2012;Stickley et al, 2010). Muir and Laxton (2012) indicated that although service users have long been involved in the training of medical students, they play a passive role in assessments.…”
Section: Key Themes From the Literature Reviewmentioning
confidence: 99%
“…The presented evidence in the present study suggests a high degree of positivity towards involving users in the planning delivering and reviewing of all areas of mental health service provision, including undergraduate preparatory programmes provided through university faculties (Simpson et al . 2008, Collier & Stickley 2010, Dearnsley et al . 2011, Happell et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, both Felton and Stickley (2004) and Wood and Wilson-Barnett (1999) suggest that issues around power and control still need addressing in order to achieve good collaborative working relationships between the professionals and service users. Dearnley et al (2011) discuss some of the benefits and challenges that are inherent in the involvement of service users in practice assessment and suggest that to engage service users who have not been adequately prepared for the role is both unethical and unreliable. There was also considerable evidence that practice educators were acting as gatekeepers and in several instances not allowing the student to seek this feedback.…”
Section: Discussionmentioning
confidence: 98%